2019
DOI: 10.5888/pcd16.180282
|View full text |Cite
|
Sign up to set email alerts
|

Tapping Into Multiple Data “Springs” to Strengthen Policy Streams: A Guide to the Types of Data Needed to Formulate Local Retail Tobacco Control Policy

Abstract: In 2015, the tobacco industry spent $8.24 billion to market tobacco products in convenience stores, supermarkets, pharmacies, and other retail or point-of-sale settings. Community tobacco control partnerships have numerous evidence-based policies (eg, tobacco retailer licensing and compliance, tobacco-free–school buffer zones, eliminating price discounts) to counter point-of-sale tobacco marketing. However, deciding which point-of-sale policies to implement — and when and in what order to implement them — is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(34 reference statements)
0
2
0
1
Order By: Relevance
“…In an attempt to formulate tools that can be used within the scope of public policies to restrict selling points, it was found that increasing the price of tobacco products is the most effective way to reduce overall consumption and that the distance from selling points of schools must be expanded. In addition, greater surveillance is needed in relation to current bans, particularly as advertisement density near schools has been associated with student use outcomes (MYERS et al, 2019;PHETPHUM;NARONGSAK, 2019).…”
Section: Density Of Selling Points Consumption Of Tobacco Products An...mentioning
confidence: 99%
“…In an attempt to formulate tools that can be used within the scope of public policies to restrict selling points, it was found that increasing the price of tobacco products is the most effective way to reduce overall consumption and that the distance from selling points of schools must be expanded. In addition, greater surveillance is needed in relation to current bans, particularly as advertisement density near schools has been associated with student use outcomes (MYERS et al, 2019;PHETPHUM;NARONGSAK, 2019).…”
Section: Density Of Selling Points Consumption Of Tobacco Products An...mentioning
confidence: 99%
“…Na tentativa de formular ferramentas que podem ser utilizadas no âmbito das políticas públicas para restrição de pontos de vendas, constatou-se que aumentar o preço dos produtos do tabaco é a forma mais eficaz de reduzir o consumo geral e que a distância dos pontos de vendas das escolas deve ser expandida. Além disso, é necessária maior fiscalização em relação às proibições atuais, principalmente porque a densidade de anúncios perto das escolas foi associada aos resultados do uso pelos alunos (MYERS et al, 2019;PHETPHUM;NARONGSAK, 2019).…”
Section: Densidade De Pontos De Venda Consumo De Produtos Derivados D...unclassified
“…In their discussion of strengthening policy streams for tobacco control, Myers et al (2019) describe the importance of naming public health impact and including supporting citations that outline how the proposed policy will lead to the health benefit. Given the potential use of e-cigarettes as harm reduction devices for adult smokers and the reluctance of legislators to interfere with individual rights, advocates, and policymakers will likely need to use the literature to demonstrate a policy will actually address its stated goal, if meant to address youth vaping.…”
Section: Implications For Researchmentioning
confidence: 99%